Progress in defining the significance of intraspecific variation to the success of the Argentine stem weevil parasitoid in New Zealand - Phillips, C.B.; McNeill, M.R.; Cane, R.P.; Goldson, S.L. (New Zealand Plant Protection, 2000)
Releases of eight South American geographic populations of the parasitoid Microctonus hyperodae Loan (Hymenoptera Braconidae) began in New Zealand in 1991 to assist in the suppression of the pasture pest Listronotus bonariensis (Kuschel) (Coleoptera Curculionidae) A morphometric analysis of M hyperodae adults collected from five of the New Zealand release sites during 199294 indicated that parasitoids derived from west of the South American Andes were significantly less successful than those from east of the Andes It was postulated that parasitoids from west of the Andes were either poorly adapted to New Zealand conditions and unable to establish or were reasonably well adapted to New Zealand conditions but were slightly less competitive than parasitoids from east of the Andes Preliminary results from a field experiment where parasitoids from east and west of the Andes were released separately strongly support the latter possibility